Arte Moderna, Trabalho e Resgate Humanístico do Cotidiano na Capela do Cristo Operário: São Paulo, 1951-1967 - Claro, Mauro; Szmerecsanyi, Maria Irene (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1995)
This paper analyses an attem pt of improvement of manual workers' life by means of mobilisation of their aesthetic sense. The doctrinary work was based on three main points: the formation of aesthetic patterns founded on modernism; the self-gestionary management of a capitalist enterprise; the transmission of catholic moral patterns according to the social humanistic interpretation current soon after the 2nd world war. This appropriation of aesthetic means by a social project makes clear the utopic dimension inherents to the modern m ovement in the arts